Ялтинская конференция 1945 г.: в гносеологическом поле философии - Шевченко, О.К. (Культура народов Причерноморья, 2013)
В предлагаемой статье исследуются параметры философского освоения Крымской (Ялтинской) конференции 1945 года. Анализируются структурные элементы специфического философского познания Ялты-45. Систематически вскрываються предельные основания философских познавательных практик в «Ялтинских студиях». Статья предназначена как для философов интересующихся Крымской конференции, так и для историков (политологов, специалисто- международников) профессионально изучающих феномен Ялтинских договоренностей. У пропонованій статті досліджуються параметри філософського освоєння Кримської (Ялтинської) конференції 1945 року. Аналізуються структурні елементи специфічного філософського пізнання Ялти-45. Систематично висвітлюються граничні засади філософських пізнавальних практик в «Ялтинських студіях». Стаття призначена як для філософів Кримської конференції, що цікавиться, так і для істориків (політологів, фахівців-міжнародників) професійно вивчаючий феномен Ялтинських домовленостей. In this paper we investigate the parameters of the philosophical development of the Crimean ( Yalta) Conference 1945. Analyzes the structural elements of a specific philosophical knowledge of Yalta -45 . Systematically opened the ultimate foundations of philosophical cognitive practices in the " Yalta studios ." The philosophical analysis of it in several areas of philosophy : logic and rhetoric , and Epistemology Epistemology , Social Philosophy , Axiology and Philosophical Anthropology, Aesthetics and Cultural Studies . The most important issues of philosophical knowledge of the Yalta Conference confession: 1) Logical analysis of event-related forms of the Yalta Conference. 2) Paradoxes of the Yalta Conference in 1945 3) Samples of rhetorical devices at the Yalta Conference. 4) Key categories and concepts of semantic structures " Yalta agreements ." 5) Credibility as a factor in the historical analysis of documents " Yalta Conference ". 6) Synergy , causality and coherence - in a holistic perception of micro-and macro-story events Yalta negotiations. 7) Parameters and levels of axiological consideration of agreements at the Yalta Conference . 8) The dilemma desirable and accessible , affordable and appropriate for compromises in Yalta. 9) The concept of "Justice" in addressing the key issues of the Crimean conference. Yalta Conference as an artistic image. 10) Ideal forms of the Crimean Conference in painting, sculpture , literature, photography 11) Yalta Conference and the categories of aesthetics , " uplands and lowlands ," " beautiful and the ugly ," " The tragic and the comic ." This article is intended for philosophers interested in the Yalta Conference , and for historians ( political scientists, specialists in international relations ) professionally learning phenomenon of the Yalta agreements.
Remove selected